Pirfenidone Has Anti-fibrotic Effects in a Tissue-Engineered Model of Human Cardiac Fibrosis - Bracco Gartner, Thomas C. L.; Crnko, Sandra; Leiteris, Laurynas; van Adrichem, Iris; van Laake, Linda W.; Bouten, Carlijn V. C.; Goumans, Marie José; Suyker, Willem J. L.; Sluijter, Joost P. G.; Hjortnaes, Jesper (Frontiers in Cardiovascular Medicine, 2022)
A fundamental process in the development and progression of heart failure is fibrotic remodeling, characterized by excessive deposition of extracellular matrix proteins in response to injury. Currently, therapies that effectively target and reverse cardiac fibrosis are lacking, warranting novel therapeutic strategies and reliable methods to study their effect. Using a gelatin methacryloyl hydrogel, human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) and human fetal cardiac fibroblasts (hfCF), we developed a multi-cellular mechanically tunable 3D in vitro model of human cardiac fibrosis. This model was used to evaluate the effects of a promising anti-fibrotic drug—pirfenidone—and yields proof-of-concept of the drug testing potential of this platform. Our study demonstrates that pirfenidone has anti-fibrotic effects but does not reverse all TGF-β1 induced pro-fibrotic changes, which provides new insights into its mechanism of action.